The capacity of working memory during Problem’s solving for the university students - Al-Abdullah, Sarah Thamer Khadim; Al-Abasi, Shaymaa Abdull Aziz (Al-Adab Journal, 2021)
The current study aims to identify: The Working memory capacity in problem solving for the students of the university. The Differences in Working memory capacity in problem solving the students of the university due to the variables gender (male- female) and specialization (human science) In order to achieve the objectives of the research, the researchers built a tool for the purpose of measuring the (Working memory capacity in problem solving), depending on the theoretical framework of the theory of(Baddeley,2000) (memory capacity in problem solving), and after we verify the researchers of the properties Alsekoumtria of scale through the extraction of honesty and strength discriminatory and coefficient of correlation between the degree of the paragraph and class College of the scale, with a constant measure of Working memory capacity in problem solving (0,74), in a re-test, and (0.77) in a manner Alpha Cronbach, and the number of paragraphs of the scale, (10) paragraph, the researchers applied the scale on a random sample of university students at (600) students The student, according to the variable type (male, female), specialty (scientific, humanistic), grade (second-fourth), and after data collection and processing statistically using the T. test for one sample, the T. test for two samples independent, Pearson correlation coefficient, reach researchers to the following: 1.Have the current research sample Working memory capacity in problem solving. 2. statistically significant in the Management of Working memory capacity in problem solving the students of the university depending on the type variables (males - females) for males and specialization (scientific - Humanist) for scientific. The research came out a set of recommendations and proposals.